Uma forma colorida de falar: estudo sociolinguístico do léxico gay em Belo Horizonte - MG - Gilmar Araujo de Oliveira (2023)
This study proposes reflections on the lexicon used among gay men, aged between 18 and over 50, in the city of Belo Horizonte - MG, using a sample of fourteen gay men to build the corpus, with the aim of identifying and analyzing, based on semi-structured interviews, the lexemes used in the speech of this group, pointing out yet another form of language variation, with linguistic facts that can be interpreted as characteristics of gay speech. The hypothesis raised in this research is that the speech used by gay men is a social and sexual mark, and that there is a need to describe the linguistic data used by people from this community. The work is structured from the study of linguistic variation and change, from a perspective originating from Weinreich, Labov and Herzog (2006 [1968]), followed by the presentation of linguistic variation at the lexical level (BIDERMAN, 2001), as well as a historical journey through the structuring of the LGBTQIAPN+ movement in Brazil (GREEN, 2019), including studies on the arrival of this movement in Belo Horizonte (MACHADO, 2007). The way homosexuals speak is a sign of resistance and social identification, since LGBTQIAPN+ people are discriminated against by society and use countless strategies to survive the constant attacks. As well as studying the speech patterns of homosexuals, this research aims to be a way of reducing prejudices against this group in question. The gay men who took part in this research stand out socially because of the way they express themselves and are evaluated on a daily basis by their interlocutors, and these language characteristics deserve the attention of this sociolinguistic study, since the way individuals speak, regardless of color, ethnicity or sexual orientation, should be known and, above all, respected. The identification of the gay lexicon took place through three interviews, through different focus groups - with an age range (18 to over 50), from which seventy-two lexemes were identified, which reveal the search for a certain cultural identity of their own, as a result of the discrimination suffered and still suffered by gays. A comparative spreadsheet was drawn up with information gathered from four Portuguese language dictionaries and it was identified that forty-four lexias have not been dictionarized. This made it possible to create a glossary including these lexias. Finally, it was found that there are differences and similarities that mark the way gay men of different age groups speak, and this demonstrates a strengthening and affirmation that there is a colorful way of speaking.